Utilization of Learning Management System-Based Moodle and Google Classroom for Arabic Language Learning - Fadhil Izzan JM; Muhammad Bilal; Fathul Maujud (Sustainable, 2025)
This study investigates the integration of Learning Management Systems (LMS), particularly Moodle and Google Classroom, in Arabic language education through a systematic literature review. The article search was conducted between 2019 and 2025 across Google Scholar databases using keywords related to Arabic language learning, Moodle, Google Classroom, and digital pedagogy. The initial search yielded 143 publications, of which 123 met the inclusion criteria through title and abstract screening, and 20 studies that fulfilled eligibility criteria were analyzed in full. The synthesis of the selected articles shows that LMS significantly improves accessibility, interactivity, and student engagement through flexible, structured, and multimedia-based learning environments. However, several constraints persist, including reduced learner motivation, insufficient digital competence among teachers, unequal access to technology, and limited opportunities for authentic muhādatsah practice. The findings highlight that the effectiveness of LMS depends heavily on teachers’ digital readiness, the availability of contextualized digital learning materials, and institutional support to sustain technological innovation. Overall, blended learning and LMS-supported instruction have strong potential to enhance communicative competence and independent learning skills, provided that pedagogical reform and capacity building are ensured.